ROLE AND KEY SUCCESS OF AGROFORESTRY (A REVIEW) - Ary Widiyanto; Aditya Hani (Balai Litbang Teknologi Agroforestry, Ciamis, 2021)
An increase in the population has led to an increase in the need for food, land for cultivation, residential land, and land for industry. One effort to accommodate the interests of the community towards the needs of agricultural land is by implementing an agroforestry system. Agroforestry systems are sustainable agricultural systems because of the combination of plants with various types and have several canopy strata that are more environmentally friendly. However, there are still many agroforestry practices that still have low productivity. So that farmers are not interested in developing them. Agroforestry has some superior characteristics compared to the traditional farming system (monoculture) in economic, social, and environmental aspects. Agroforestry can succeed if it can increase community income while maintaining land productivity. The success of agroforestry is influenced by: a) selection of the right type of plant, b) maintenance of plants, c) marketing and processing of products d) strong farmer institutions.